Mengurai Sosiologi Empiris Berger dan Luckmann sebagai Konstruksi Pengetahuan - Marde Christian Stenly Mawikere; Sudiria Hura (Tumou Tou, 2022)
This article describes the theory of the sociology of knowledge from Peter Berger and Thomas Luckmann which is reviewed in their best-selling book entitled “The Social Construction of Reality:  A Treatise in the Sociology of Knowledge”. The research was conducted by conducting a "book review" on the substance of Berger and Luckmann's ideas about social construction based on reality, especially regarding the construction of knowledge. Berger and Luckmann argue that knowledge as reality is the result of individual struggles in daily life experiences where there is always a dialectic between objective and subjective elements and a dialectic between the dimensions of internalization, objectivation and externalization processes that make meaning in human existence. Thus the sociology of knowledge advocated by Berger and Luckmann includes knowledge as a result of reflection on individual experiences in their environment and community which can also be called "empirical sociology". The relevance of such a theory of knowledge construction provides significance and a foothold for humans as learners and the idea of independent learning.